PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Rudiansyah '; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) To identify the role of extension on independent small holder farmers of oil palm; (2) To know empowerment level of the farmers; (3) To analyze the aims of extension; (4) To analyze influence the role’s of extension toward empowerment and influence empowerment toward the aims of extension. This research was conducted at Betung Village and Batang Kulim Village in Pangkalan Kuras Sub District Pelalawan District. Research’s respondent was determined by purposive sampling methods with number of respondent were 120. The consideration to choose the location is the location that has active extension activities and has farmer group. Validity, reliability, outliers, normality and multicolinearity analysis has been done on the measuring instruments. To answer the first, second, and third purpose of this research using likert’s scale summated rating (SLR). To answer the fourth research purpose was using structural equation modeling (SEM) with the AMOS program. The result shows (1) The role of extension has shown quite on independent small holder farmers activity; (2) The empowerment level of farmers on the categorize quite with the extension activities as seen from empowerment human resource, productive economy, and the farmers institutional; (3) The aims of extension has quite as seen from better farming, better business and better living; (4) the role of extension has proven directly influence significantly toward level of farmer’s empowerment and the level of farmer’s empowerment has proven directly influence significantly toward reach of the role extension aims. Key words: The role of extension, empowerments, extension aims, independent small holder, oil palm